(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
The topic of this interdisciplinary work is the relationship between love and money in Serbian and Spanish paremias, with the aim of shedding light on the similarities and differences between Serbian and Spanish society, which are woven into these paremias under the influence of social, cultural and historical factors. Qualitative sociolinguistic and comparative methods were used. In the analysis of the corpus we find two contradictory ideas: 1) money cannot affect the quality or duration of love, 2) love depends on the material situation, lack of money weakens or extinguishes love. We can assume that these two peoples went through difficult economic periods for the common man and hence the paremias that favor money over love.